Managing reactive nitrogen in spring wheat cropping systems: insights from Kabul, Afghanistan - Zikrullah Safi; Robert Rees; Julia Drewer; Arti Bhatia; Tapan Kumar Adhya; Abdul Wakeel; Sangeeta Bansal (Environmental Research Communications)
Ammonia (NH _3 ) volatilization and nitrate leaching are significant pathways of reactive nitrogen (N r ) losses in agriculture, leading to environmental concerns. This study investigates nitrogen (N) losses in wheat production near Kabul, Afghanistan, aiming to improve nitrogen use efficiency (NUE) for food security and environmental protection. Three fertilizer treatments were tested: (A) animal manure (2 t h ^−1 ) + 50% chemical fertilizer (urea and diammonium phosphate, DAP), (B) night soil (2 t ha ^−1 ) + 50% chemical fertilizer, and (C) full dose of chemical fertilizer, with sub-treatments varying in N application (25% less, 25% excess, and farmers’ practice). A no-fertilizer control treatment was included. Ammonia emissions and nitrate-N (NO _3 -N) and ammonium (NH _4 -N) leaching were monitored, and NUE was calculated. Subsurface application (treatment A _2 ) reduced ammonia emissions by 41.82% compared to 55% in surface applications (treatment A _3 ) and 15% in control plots. Ammonium-N losses were lower in subsurface application (31%) than surface applications (53%). NUE was highest in surface application (103%) and lowest in subsurface (84%). Moreover, Partial Factor Productivity (PFP) was higher in treatments with 25% less N compared to those with 25% excess and conventional practice. The novelty of this study lies in the implementation of subsurface application techniques to reduce N losses and enhance NUE in this region, where such techniques are rarely used. These results offer a model for improving NUE by optimizing fertilizer and manure inputs, applicable to similar agricultural systems globally.